Survei Faktor-Faktor yang Mempengaruhi Minat Olahraga Rekreasi Akhir Pekan di Alun-Alun Wonosobo - Kusuma, Bayu Aji (Department of Physical Education, Sport, Health and Recreation, 2016)
The purpose of this study was to determine the factors are that affect the interests of recreationalsports weekend were done by the people in the square Wonosobo in 2014 as well as howbig the factors that affect interest in doing recreational sports weekend in the square Wonosobo2014 .This method used was a survey research, data collection method using observations observationand questionnaires. Results of research on the factors that affect interest in selectingsports weekend dialun main Wonosobo district showed that the number of people who havean interest to exercise dialun the central district of Wonosobo included in the high category.The high factors that influence society to exercise dialun the central district of Wonosoboamong other physical factors, psychological factors, factors relations or relations of familymembers, factor atmosphere of the house, socio-economic conditions, factors of work, job satisfactionfactors, factors work motivation, factors employment benefits, environmental factorsresidence. Based on the results of research and discussion can be concluded that the factorsthat affect interest in recreational sports weekend were done by the people in the square Wonosobois the physical, psychological, relationship of family members, the house, socio-economicconditions, employment, job satisfaction, work motivation, the benefits of working and livingenvironment.